1997
DOI: 10.1128/jb.179.13.4299-4304.1997
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic regulation of isocitrate dehydrogenase gene (icd) expression in Escherichia coli by the arcA and fnr gene products

Abstract: Isocitrate dehydrogenase, the icd gene product, has been studied extensively regarding the regulation of enzymatic activity and its relationship to the metabolic flux between the tricarboxylic acid cycle and the glyoxylate bypass. In this study, the transcriptional regulation of icd gene expression was monitored by using an icd-lacZ gene fusion and shown to vary over a 15-fold range in response to changes in oxygen and carbon availability. Anaerobic cell growth resulted in fivefold-lower icd-lacZ expression th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 32 publications
7
44
0
Order By: Relevance
“…Similar observations were made for several other TCA cycle genes, including gltA, mdh, fumA and icd Woods and Guest, 1994;Park and Gunsalus, 1995;Park et al, 1995b;Chao et al, 1997), as well as for some respiratory pathway genes, frdABCD, dmsABC and narGHJI (Jones and Gunsalus, 1987;Li and DeMoss, 1988;Cotter and Gunsalus, 1989;reviewed in Gunsalus and Park, 1994). The molecular basis for this ArcA-and Fnr-independent control is not well understood, but it may be related to minor effects of DNA supercoiling (Axley and Stadtman, 1988).…”
Section: Fnr Acts As a Negative Regulator Of Sdhc Promoter Expressionsupporting
confidence: 58%
“…Similar observations were made for several other TCA cycle genes, including gltA, mdh, fumA and icd Woods and Guest, 1994;Park and Gunsalus, 1995;Park et al, 1995b;Chao et al, 1997), as well as for some respiratory pathway genes, frdABCD, dmsABC and narGHJI (Jones and Gunsalus, 1987;Li and DeMoss, 1988;Cotter and Gunsalus, 1989;reviewed in Gunsalus and Park, 1994). The molecular basis for this ArcA-and Fnr-independent control is not well understood, but it may be related to minor effects of DNA supercoiling (Axley and Stadtman, 1988).…”
Section: Fnr Acts As a Negative Regulator Of Sdhc Promoter Expressionsupporting
confidence: 58%
“…3B), as shown previously (16,60,63). Although expression of genes encoding TCA cycle enzymes was shown to be increased 6-to 70-fold in ArcA mutants during anaerobic growth (9,(44)(45)(46)(47)(48) and in vitro TCA cycle enzyme activities were indeed increased in the ArcA mutant (Table 4), the in vivo TCA flux could not be higher in the mutant because the concomitantly generated NADH could not be reoxidized. In the presence of exogenous electron acceptors, however, this was feasible.…”
Section: Metabolic Impact Of Global Regulator Knockoutsmentioning
confidence: 66%
“…Generally, the Arc (anoxic redox control) two-component system is considered to be a global transcriptional regulator in response to the redox conditions and in particular to deprivation of oxygen under microaerobic conditions (2,22,28,37). Although the expression of the TCA cycle genes gltA, icdA, sdhCDAB, fumA, and mdh was known to double in fully aerated ArcA mutants (9,(45)(46)(47)(48), previous flux (2) and phosphorylation data for the sensor kinase ArcB (22) suggested that ArcA regulation did not affect aerobic glucose catabolism. While ArcA is clearly active under fully anaerobic conditions (36), Arc-dependent regulation can modulate anaerobic TCA cycle fluxes only in the presence of electron acceptors that reoxidze the concomitantly generated reducing equivalents.…”
Section: Discussionmentioning
confidence: 99%
“…We used the isocitrate dehydrogenase promoter (P icd ) to control the expression of glpK. This promoter would express glpK strongly during the aerobic preculture stages and then reduce glpK expression during the microaerobic fermentation through the arcA and fnr gene products (21). The use of these promoters gave us the expression profiles that we wanted without the need for inducers.…”
Section: Discussionmentioning
confidence: 99%